Why social values cannot be changed for the sake of conservation. Issue 4 (13th February 2017) - Manfredo, Michael J.; Bruskotter, Jeremy T.; Teel, Tara L.; Fulton, David; Schwartz, Shalom H.; Arlinghaus, Robert; Oishi, Shigehiro; Uskul, Ayse K.; Redford, Kent; Kitayama, Shinobu; Sullivan, Leeann
Abstract: The hope for creating widespread change in social values has endured among conservation professionals since early calls by Aldo Leopold for a "land ethic." However, there has been little serious attention in conservation to the fields of investigation that address values, how they are formed, and how they change. We introduce a social–ecological systems conceptual approach in which values are seen not only as motivational goals people hold but also as ideas that are deeply embedded in society's material culture, collective behaviors, traditions, and institutions. Values define and bind groups, organizations, and societies; serve an adaptive role; and are typically stable across generations. When abrupt value changes occur, they are in response to substantial alterations in the social–ecological context. Such changes build on prior value structures and do not result in complete replacement. Given this understanding of values, we conclude that deliberate efforts to orchestrate value shifts for conservation are unlikely to be effective. Instead, there is an urgent need for research on values with a multilevel and dynamic view that can inform innovative conservation strategies for working within existing value structures. New directions facilitated by a systems approach will enhance understanding of the role values play in shaping conservation challenges and improve management of the human component of conservation.